IMPLEMENTASI HADIS NIAT DALAM PEMBENTUKAN MOTIVASI BELAJAR SANTRI DI PONDOK PESANTREN MAHASANTRI BAITUL ILMI JEMBER - Fikriyah Hanim; Abdullah; Matkur (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
Sincere intention for Allah is the main foundation in studying in Islamic boarding schools, distinguishing the blessings and benefits of knowledge obtained by students, and determining the value of each deed as emphasized in the hadith of the Prophet Muhammad SAW: